Implementasi Aliran Konstruktivisme Terhadap Kurikulum Merdeka Dalam Perspektif Filsafat Pendidikan Islam - Refi Mariska; Abdul Khobir (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This research discusses the flow of constructivism from the perspective of Islam education philosophy. The latest curriculum update, namely the independent learning curriculum, which is linked to constructivism, is the reason for this research, because in the independent learning curriculum, learning is more student-centered, so constructivist learning plays a big role in it. This research uses qualitative methods with a library research approach. Data collection techniques through library sources related to research related to research titles from books, journals, articles and other related writings. The results of the research show that the constructivist school can be used in the learning process in accordance with the independent learning curriculum which is currently still being implemented where students can develop their own existing knowledge based on experience.